Prevalence of Malaria and Associated Factors among Malaria-Suspected Patients Attending Hamusit Health Center, Northwest Ethiopia: A Cross-Sectional Study - Getu Abeje Negatu; Getaneh Alemu Abebe; Woynshet Gelaye Yalew (Journal of Parasitology Research)
Background. Malaria is one of the major public health problems in developing countries like Ethiopia. Despite efforts to reduce the mortality and morbidity, the disease is still a prominent health problem in Ethiopia. This study, therefore, was undertaken to assess the prevalence of malaria and associated factors among symptomatic patients in Northwest Ethiopia. Methods. A facility based cross-sectional study was conducted from February to March 2020 among 210 febrile patients attending Hamusit Health Center, Northwest Ethiopia. A structured questionnaire was used to collect data on sociodemographic characteristics and factors perceived to be associated with Plasmodium infection. Questionnaire data was collected through face to face interview. Thin and thick blood films were prepared from capillary blood buffy coat samples. Data were analyzed using Statistical Package for Social Sciences Software version 20. Results. Out of 210 malaria-suspected participants, 61 (29.0%) were confirmed to be infected by Plasmodium species. Plasmodium falciparum and P. vivax monoinfections were detected in 41 (19.5%) and 10 (4.8%) participants, respectively. Mixed infection was detected in 10 (4.8%) participants. Female participants (AOR=2.261; 95% CI: 1.118-4.571; P=0.023) and those having family members with history of malaria (AOR =2.261; 95% CI: 1.264-5.340; P=0.009) had higher odds of acquiring Plasmodium infection as compared to their counterparts. Using insecticide-treated bed net and draining stagnant water were the most commonly mentioned malaria prevention measures reported by 71.9% and 8.1% of the respondents, respectively. Conclusion. Malaria contributes significantly for febrile illnesses in the study area. Therefore, community mobilization should be strengthen in order to improve implementation of malaria control activities and, hence, reducing the prevalence.